Targeting anti-virulence factor strategies of bacterial pathogens - Jiashu Li; Tianyuan Jia; Liang Yang (Biosafety and Health)
Antibiotic-resistant bacterial pathogens pose substantial biosafety and health hazards, leading to millions of deaths each year. The evolution of bacterial virulence factors is mainly propelled by horizontal gene transfer (HGT). In addition to traditional antibiotics, antimicrobial strategies targeting biofilm-related virulence factors and quorum sensing (QS)-related virulence factors can effectively restrain drug-resistant bacteria. Future anti-virulence strategies, encompassing natural drugs, antibiotic resistance inhibitors, monoclonal antibodies (mAbs), and vaccines, are in the development pipeline. Consequently, by disrupting virulence factors, these drugs can eliminate the ability of bacterial pathogens to cause disease. In conclusion, this Perspective comprehensively summarizes current anti-bacterial virulence factor strategies and prospects for future cutting-edge approaches, which may address the issues of antibacterial resistance and curtail the spread of pathogens in the future.